Analyzing the relationship dynamics between contributors and corporate influence within Free and/or Open Source communities using the Multi Faceted Trust/Distrust theory and its implications for fostering better relationship solutions - Lim, Song Jun (2008)
Corporations and F/OSS movements have been known to at opposites with each other. Once, the F/OSS movement was considered to be a sub culture movement dominated by computer enthusiasts keen on working on their hobby, anything computer related. Corporations however act on the interest of producing profit. Of late, due to advancement of technology especially in the areas of communication, the access of a wide base of knowledge and expertise has resulted in mass collaboration of production and consumption. Geographic boundaries of resource access, especially in knowledge based resources and skills, are now almost irrelevant. As such, there is a wide application for this mass collaborative model in software production. Building on the hobbyist sub culture, corporations now seek to engage these highly motivated knowledge experts in an effort to tap into this wide pool of resources. The emergence of F/OSS based companies that utilize F/OSS communities show it is possible to tap into the hobbyist community network. Hence, formal corporate sponsorship of F/OSS communities and projects are now the rising norm. However, corporate and hobbyist interests are mired by conflicting ideals and principles, causing constant clashes between the two. This paper therefore aims to investigate the complex of how contributors deal and relate to having corporate influence trust upon what was once their own domain. This leads to several questions, how do volunteer contributors view and interact with corporate employed contributors? Would they distrust them and view them as part of the corporate machinery or identify with them as fellow contributor? Furthermore, how do contributors overcome their distrust for corporations when contributing towards sponsored communities? How do corporations affect the community when distrust exists in the community? This paper seeks to investigate the dynamics of individual contributor trust/distrust relations between corporate figures to further our understanding of community vs corporation relationships. As such, I utilize trust/distrust theory in an effort to determine the relational dynamics, and the negative consequences of distrust. I use a combination of qualitative and quantitative research in gathering an understanding behind the rationality of contributors in engaging with corporate entities. Results from an empirical analysis of two F/OSS projects which were facing trust issues show that contributors both trust and distrust corporate sponsored communities. I use the results to form deductions which are then applied using Lewicki et al's (1998) research on trust and distrust. It was deduced that contributors might view community and corporation as two separate entities, allowing them to place enough trust to participate yet retain their distrust for corporate authority. I found that sponsored communities consists of three types of contributors based on their motivations. It was also found that distrust causes irrational assumptions that result in contributors wanting to disassociate themselves from the community. I conclude with some recommendations on how to avert community desertion